The Effect of Flashcard Learning Media in Developing Cognitive Children Aged 5-6 Years in Al-Mauizhah Kindergarten, Silau Jawa Village, Bandar Pasir Mandoge District, Academic Year 2022/2023 - Nurul Husna Saragih; Kamtini (Indonesian Journal of Advanced Research, 2023)
This study aims to determine the effect of using flashcard learning media in developing the cognitive development of children aged 5-6 years in Al-Mauizhah Kindergarten, Silau Jawa Village, Bandar Pasir Mandoge District, Academic Year 2022/2023. This type of research is a quantitative research (quasi experiment) with the form of One Group Pretest-Posttest Design. The population of this study were all class B children at Al-Mauizhah Kindergarten, Silau Jawa Village, Bandar Pasir Mandoge District, 2022/2023 Academic Year, with a total of 30 children. The sampling technique is by looking at the list of the lowest scores from the teacher's data, namely 10 children. The data collection instrument in this study used observation and documentation sheets. Data analysis technique using non-parametric statistical Wilcoxon test. The results showed that the flashcard media from the calculation of the Wilcoxon Rank-K Test, the Z value was close to -2.825b and the p value (Asymp.Sig 2-tailed) was close to .005. It can be concluded that the "Hypothesis is accepted" because the number .005 is smaller than 0.05. There are differences in the results between the results of the use of flashcard media in the pretest and posttest, so it can be concluded that the use of flashcard media has an effect. about the Cognitive Development of Children Aged 5-6 Years in Al-Mauizhah Kindergarten, Bandar Pasir Mandoge Village, Academic Year 2022–2023.